2013
DOI: 10.1589/jpts.25.611
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Behavior Training for Stroke Patients Using Action Observation and Practice of Upper Limb Function

Abstract: [Purpose] This study examined the effects of action observation and action practice on stroke patients’ upper limb function. [Subjects and Methods] The subjects were 33 chronic stroke patients who were randomly assigned to four groups. The action observation group (5 males, 3 females) watched a video of the task, the action practice group (5 males, 4 females) performed the action, the combined action observation-action practice group (5 males, 4 females) watched the video of the task and practiced the action, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 8 publications
4
46
1
1
Order By: Relevance
“…These results suggest that action observation training can be a more useful intervention method than task-oriented training for improving the motor skills of patients with impaired motor skills due to damage to the brain region such as that resulting from a stroke 11 ) . Recently, evidence has been presented supporting the effects of action observation training in the process of relearning functional tasks after a stroke 12 ) , and proposals indicating that larger improvements in skills can be expected if action observation training is applied to patients in combination with the training currently used in interventions for rehabilitation have been raised 13 , 14 ) .…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that action observation training can be a more useful intervention method than task-oriented training for improving the motor skills of patients with impaired motor skills due to damage to the brain region such as that resulting from a stroke 11 ) . Recently, evidence has been presented supporting the effects of action observation training in the process of relearning functional tasks after a stroke 12 ) , and proposals indicating that larger improvements in skills can be expected if action observation training is applied to patients in combination with the training currently used in interventions for rehabilitation have been raised 13 , 14 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Two studies 7 , 12 ) used the Fugl-Meyer assessment (FM) and the Box and Block Test (BBT), one study 9 ) used the Motricity Index (MI) and the Action Research Arm Test (ARAT), and one article 10 ) used the Wolf Motor Function Test (WMFT) as the outcome parameter, whereas the study of Lee et al 11 ) evaluated outcome with an analysis of drinking behavior. Four 7 , 10 , 11 , 12 ) of the RCTs reported statistically significant effects for motor recovery of upper limb, whereas 1 RCTs 9 ) did not find significant differences between groups. The experimental group received an AO intervention 30 to 60 minutes per day, 3 to 5 times per week, for a total of 15 to 20 sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Ertelt et al 10 ) reported that AO had a significant effect of patients with chronic stroke, and Franceschini et al 7 ) investigated the effect of AO on patient with acute stroke. Lee et al 11 ) did not report the conditions after stroke. Future systematic review or meta-analysis with pooled data analysis would prove useful in determining the effectiveness of the conditions (acute and chronic) after stroke and duration of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The manner of active error detection based on observational learning has been classified into three types based on previous studies: model-observation (MO) 11 ) , where the patient observes the ideal model movement; self-observation (SO) 12 ) , where the patient observes their own movement; and the model and self-observation (MSO), which is a combination of MO and SO. MO has also been defined as action observation 13 , 14 ) , where an observer can understand what other people are doing by simulating the actions and the outcomes that are likely to follow from the observed motor act 13 , 15 , 16 ) . In particular, the method of referring to another person’s image has been regarded as MO.…”
Section: Introductionmentioning
confidence: 99%